Effect Concentration of Moringa (Moringa oleifera Lam) Leaf Extract in Citrate-Egg Yolk in Maintaining Motility and Viability of Spermatozoa of Kacang Goat - R. R. Dapawole; I. P. Sirappa (Jurnal Sain Peternakan Indonesia, 2021)
This study aimed to determine the effectiveness and the best concentration of Moringa leaf extract (MLE) in the citrate-egg yolk (C-EY) to maintain the motility and viability of spermatozoa kacang goat. Semen was collected from 3 goats aged two years; by using the artificial vagina method. The semen was evaluated macroscopically and microscopically. The semen that had >70% sperm motility and >250x106/ml sperm concentration was divided into 4 equal tubes, each diluted with100% C-EY (P1), 10% MLE+ 90%C-EY (P2), 20% MLE +80% C-EY (P3), and 30% MLE+70% C-EY (P4). The diluted samples were then stored in a refrigerator (3-5?C) and evaluated for motility and viability every 24 hours. The study was designed using a completely randomized design (CRD) consisting of four treatments and five replications. The results showed that the addition of MLE in C-EY significantly affected goat spermatozoa's progressive motility and viability. The data showed that the spermatozoa kept during four days in a diluent of P2 had higher (P<0.05) motility 44.67±4.80% and viability 74.24±4.46%than the other three diluents of P1(36.00±4.70%; 70.10±3.6%), P3(33.67±0.42%; 66.85±4.99%) and P4 (29.67±3.99%; 63.96±5.44%). This study concluded that adding 10% MLE was the best concentration as source energy in 90% C-EY diluents, which effectively maintained the motility and viability of kacang goat spermatozoa for four days of storage at a temperature of 3-5oC.